On Weighted Hadamard-Type Singular Integrals and Their Applications - Yong Jia Xu (Abstract and Applied Analysis)
By means of an expression with a kind of integral operators, some properties of the weighted Hadamard-type singular integrals are revealed. As applications, the solution for certain strongly singular integral equations is discussed and illustrated.